2014
DOI: 10.1371/journal.pone.0088019
|View full text |Cite|
|
Sign up to set email alerts
|

Age-Related Decrease in the Mitochondrial Sirtuin Deacetylase Sirt3 Expression Associated with ROS Accumulation in the Auditory Cortex of the Mimetic Aging Rat Model

Abstract: Age-related dysfunction of the central auditory system, also known as central presbycusis, can affect speech perception and sound localization. Understanding the pathogenesis of central presbycusis will help to develop novel approaches to prevent or treat this disease. In this study, the mechanisms of central presbycusis were investigated using a mimetic aging rat model induced by chronic injection of D-galactose (D-Gal). We showed that malondialdehyde (MDA) levels were increased and manganese superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
66
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 63 publications
11
66
4
Order By: Relevance
“…After treated with D -gal, pathology of central presbycusis demonstrated increased neural apoptosis and neural damage as well as a decreased number of neurons in the auditory cortex and exhibited degraded cognitive function, which is similar with the natural aging process [27], [29], [30]. Additionally, our previous study also replicate the central presbycusis with D -gal and causes accumulation of the CD that was also observed in the natural aging animals [29], [31]. In our study, we explored the in vitro and in vivo mechanism for whether and how H 2 S acts on contributors of aging in the auditory cortex using a mimetic aging model induced by D -gal.…”
Section: Introductionmentioning
confidence: 71%
“…After treated with D -gal, pathology of central presbycusis demonstrated increased neural apoptosis and neural damage as well as a decreased number of neurons in the auditory cortex and exhibited degraded cognitive function, which is similar with the natural aging process [27], [29], [30]. Additionally, our previous study also replicate the central presbycusis with D -gal and causes accumulation of the CD that was also observed in the natural aging animals [29], [31]. In our study, we explored the in vitro and in vivo mechanism for whether and how H 2 S acts on contributors of aging in the auditory cortex using a mimetic aging model induced by D -gal.…”
Section: Introductionmentioning
confidence: 71%
“…A study has been reported that sirt3 expression is decreased with aging [25]. Moreover, the sirt3 coding sequence links to human aging [26].…”
Section: Discussionmentioning
confidence: 99%
“…When SIRT3 enters into mitochondria, 142 amino acids are detached from N-terminal by matrix processing peptidase and it is converted to the short active form. Studies have shown that both forms of the enzyme are functional and show enzymatic activity (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). SIRT3 regulates mitochondrial function by deacetylation of mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%